Modified basal elements in Dicroidium fronds (Corystospermales) - Bomfleur, Benjamin (2012)
We describe a distinct type of heteromorphic basal frond element in four species of the seed-fern foliage Dicroidium, based principally on a survey of plant-fossil collections from the Triassic of Antarctica. The modified foliar elements are conspicuously enlarged, and arise at wide angles and obliquely to the frond plane. Those of D. elongatum and D. crassinerve arise more or less directly from the petiole base; they are overall wedge- to fan-shaped with variably dissected margins and fan-shaped venation. Those of D. odontopteroides and D. dubium are (sub)circular, reniform, or obcordate, also with fan-shaped venation, or divided into narrow tongue-shaped segments with alethopteroid venation. The basal elements of some species commonly occur isolated. By analogy with comparable structures among other plant groups, we conclude that the basal elements represent a distinct, early leaf-ontogenetic architectural unit in the frond bauplan of Dicroidium, which provides an important additional character for a more accurate delimitation and systematic classification. Similar structures also occur on the corystosperm reproductive organs Umkomasia and Pteruchus. It appears that the basal elements were particularly common among high-latitude Dicroidium trees that flourished in a strongly seasonal light regime. We hypothesize that the modified elements may represent the initial foliar outgrowths during spring flush, ensuring a rapid re-initiation of sap flow and metabolic activity after the extended period of winter dormancy.